Individualized Parent-Mediated Behavioral Treatment for Challenging Behavior: A Program Description - Nuhu, Nadrat N.; Muething, Colin; Gillespie, Scott E.; Mevers, Joanna Lomas; Scheithauer, Mindy (Behavior modification, 2024)
Past research suggests behavioral treatments are effective for challenging behavior in children and young adults with neurodevelopmental disorders, such as autism spectrum disorder (ASD). However, access to these services can be limited and require substantial resources. To address this issue, the current study provides a programmatic description of an individualized parent-mediated service model targeting moderate challenging behavior. In the program, therapists coached parents to implement functional analyses and individualized function-based treatment packages. Forty-one families of children and young adults with neurodevelopmental disorders participated. Most clients (75.6%) met all admission treatment goals and parents reported significant decreases in frequency and severity of challenging behaviors at discharge. Parents also reported less stress at discharge. Outcomes of the study suggest this parent-mediated treatment model is a viable option to treating moderate challenging behavior in children and young adults with intellectual and developmental disorders.